MEANING AND EMBODIMENT IN RITUAL PRACTICE: with Harris Wiseman and Fraser Watts, "Spiritual Intelligence: Participating with Heart, Mind and Body"; Harris Wiseman, "Knowing Slowly: Unfolding the Depths of Meaning"; Harris Wiseman, "The Japanese Arts and Meditation‐in‐Action"; Harris Wiseman, "Meaning and Embodiment in Ritual Practice"; and Harris Wiseman, "Theoria to Theory (and Back Again): Integrating Masterman's Writings on Language and Religion." (Zygon: Journal of Religion & Science, 2022)
The article explores the interaction of verbal and nonverbal semantic levels in the performance of Christian ritual. The article maps the distinction between theoretical and performative knowledge onto Barnard and Teasdale's Interacting Cognitive Systems model to give a (partial) account of how meaning emerges in ritual participation. With Christian ritual, both know‐how and know‐that are needed. Above all, it is their interaction that generate the richness of meaning in ritual performance. Three core claims are made. First, many contemporary concepts of ritual have at least one flaw in that they do not grasp the relationality between verbal and nonverbal, wherein both dimensions have a semantic integrity of their own. Second, there is an ideological valuation of the semantic levels. The experiential level is not only meaningful in its own right, but the fundamental ground of spiritual knowing. Third, combining learning styles and kinds of attention can be valuable for eliciting the full semantic richness of ritual participation.